2002
DOI: 10.2320/matertrans.43.1873
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics-Aided Alloy Design and Evaluation of Pb-free Solders for High-Temperature Applications

Abstract: High temperature solders that will not be affected in the subsequent thermal treatment are required in the step soldering process of multi-chip module (MCM) packaging. High-Pb solder alloys such as 95Pb-5Sn (numbers are all in mass% unless specified otherwise) are currently being used for this purpose. However, the development of the Pb-free solder alloy for high temperature applications is needed due to environmental issues. The solder alloys of Bi-Ag, Sn-Sb and Au-Sb-Sn systems are considered as candidates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…[1][2][3][4][5] Au-and Bi-based alloys as representative high temperature lead-free alloys also have been faced with several serious problems during using electronic industries until now. [1][2][3][4][5][6][7] The high cost and the formation of massive intermetallic compound (IMC) or the brittle nature of Bi prevents widespread adoption of Au-and Bi-based alloys. High lead-bearing solders need to be replaced by lead-free alloys as soon as possible, because the use of high lead solder influences the recycling possibilities of electronic circuit boards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Au-and Bi-based alloys as representative high temperature lead-free alloys also have been faced with several serious problems during using electronic industries until now. [1][2][3][4][5][6][7] The high cost and the formation of massive intermetallic compound (IMC) or the brittle nature of Bi prevents widespread adoption of Au-and Bi-based alloys. High lead-bearing solders need to be replaced by lead-free alloys as soon as possible, because the use of high lead solder influences the recycling possibilities of electronic circuit boards.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional high temperature solders have been high lead-bearing alloys, typically 85-97 mass%Pb-Sn, and Au-or Bi-based alloys. [1][2][3][4][5] Over the last 10 years, scientists have made much effort in respect to developing substantially lead-free solders to replace leadbearing solders, eutectic Sn-37 mass%Pb. Successful developments have almost led to the point where lead-free electronics assembly is accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…It was 6 revealed that the addition of Sn to Bi-Ag eutectic improves its wetting on copper. The data on wetting of Cu by Bi-rich Bi-Ag alloys are limited [6][7][8][9] and differ with respect to reported values of the wetting angle. One important factor affecting quality of the joint, in particular its mechanical properties, is the structure of connection at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The type Pb-5Sn and Pb-10Sn solders are typical representatives of this group of solders with a high Pb content. Following the publications of Suganuma et al [1] and Kim et al [2] the solders based on Bi-Ag, Au-Sn, Sn-Sb, and Zn-Al alloys were selected as the basic ones for high-temperature lead-free solders.…”
Section: Introductionmentioning
confidence: 99%